Desenvolvimento, caracterização e estudo da viabilidade de micropartículas contendo Lactobacillus acidophilus La-14 obtidas por gelificação iônica externa associadas às interações eletrostáticas - Etchepare, Mariana de Araújo (2017)
Probiotics are defined by the World Health Organization as living microorganisms that when consumed in adequate amounts confer benefits to the health of the host. But for these benefits to occur, these bacteria need to get to the gut intact. Thus, the microencapsulation of probiotics has been studied in order to protect these microorganisms against adverse conditions to the medium where they are submitted. The objective of this study was to produce and evaluate calcium alginate particles in the wet and lyophilized form obtained by external ionic gelation and to coat them sequentially with multilayers of whey protein and sodium alginate in up to three layers. The effect of different numbers of layers on the viability of the free and microencapsulated culture were analyzed. The morphology and mean particle size were determined. Probiotic resistance to simulated gastrointestinal tests, heat treatments and storage viability for up to 120 days were analyzed. An efficiency greater than 80% encapsulation was obtained. The average size of the microparticles was between 107 μm and 374 μm. Lactobacillus acidophilus La-14 microencapsulated in the different treatments in the humid form was resistant during simulated gastrointestinal conditions with values above 7 log CFU g-1, whereas the lyophilized ones showed a low release, obtaining values slightly above 5 log UFC g-1. In the tests of thermal resistance the particles with multilayer presented better results in front of the free cells that did not resist. Storage for up to 120 days at refrigeration and freezing temperatures was more efficient for all types of microparticles, especially those containing multilayers, with counts above 7 log CFU g-1 for wet particles and 6 log CFU g-1 for the lyophilized, when compared to the free cells. It is concluded that the formation of the alginate and WPC multilayers produced particles resistant to the influence of the tested factors, increasing the protection for probiotics compared to the uncoated particle and, in addition, these particles can be considered as potential carriers of sensitive compounds, whose purpose is release into the intestinal environment.